The Influence of Noise Levels from Residents' Activities in the Andalas Traditional Market Area, Gorontalo City - Meidji, Icha Untari; Demulawa, Meilan; Jayadi, Harsano (Peneliti.net, 2024)
Noise problems caused by crowded urban markets make it difficult for people to find a quiet location. Andalas has many settlements, especially in the market area, which is located in urban areas and on the edge of the highway, which is also close to the market. This study aimed to determine the effect of market noise on health. The noise levels were measured using a sound meter measuring instrument, which was measured in three places: a clothing store, a fish store, and a public parking lot. Hypothesis testing was done using the chi-square statistical test with a 95% confidence level (p = 0.05).